Testing, finite element analysis and design of high strength steel RHS T-joints. (15th January 2021) - Lan, Xiaoyi; Chan, Tak-Ming; Young, Ben
Highlights: Structural behaviour and static strength of high strength steel RHS T-joints were examined. The effects of heat affected zones and suitability of CIDECT design rules were evaluated. Design rules were proposed for high strength steel RHS T-joints. The proposed strength equations produce reasonably conservative and consistent strength prediction. Abstract: This paper investigates the structural behaviour of high strength steel (HSS) rectangular hollow section (RHS) T-joints under brace axial compression. Seven fabricated RHS T-joints which were composed of built-up steel tubes with a measured yield stress of 907 MPa were tested. Extensive finite element simulations on the fabricated RHS T-joints covering a wide range of geometric parameters and steel grades ranging from S460 to S960 were conducted. The chord face plastification, chord side wall failure and a combination of these two failure modes in the fabricated RHS T-joints were examined. The effects of material softening in the heat affected zones (HAZ) on the joint behaviour and influences of the steel grade, brace to chord width ratio ( β ) and chord width to wall thickness (2 γ ) on the suitability of the CIDECT strength equations for the fabricated RHS T-joints were evaluated. The deformation capacity and ductility of test specimens are shown to be reasonably sufficient. The effect of HAZ on the initial stiffness of the fabricated RHS T-joints is insignificant. The HAZ can lower the joint strength more significantly for medium β ratio; however, the joint strength reduction is less pronounced than the material strength reduction. The CIDECT strength prediction for chord face plastification is more unconservative for higher steel grade, larger 2 γ ratio and smaller β ratio and becomes unduly conservative for the combined failure modes and chord side wall failure. It is suggested that 0.4 ≤  β  ≤ 0.85 and 2 γ  ≤ 60 β -1 for chord face plastification to allow for more effective use of HSS and corresponding reasonably conservative strength equations were proposed. Simplified strength equations which are based on an analytical model of plate buckling were proposed for chord side wall failure in the fabricated RHS T-joints with β  = 1.0 and are also applicable for cold-formed steel RHS T-joints. A linear interpolation approach using the proposed strength equations at β  = 0.85 and β  = 1.0 is recommended for the combined failure modes in the fabricated RHS T-joints with 0.85 < β < 1.0.